Prevalence And Levels of Burnout Among Nurses In Hospital Raja Perempuan Zainab II Kota Bharu, Kelantan - Zaidah Binti Mustaffa; Chan Siok Gim (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd, 2015)
The main objective of this study is to evaluate the nurses' level of burnout and identify the factors that inﬂuence it. Burnout, one such stress-related outcome, has been conceptualised as a multidimensional construct consisting of emotional exhaustion, depersonalisation and reduced personal accomplishment. Items adapted and translated from Maslach Burnout Inventory were used to collect data from 60 respondents. Among the respondents, 5.0% showed a high level of Emotional Exhaustion while 95.0% were at the moderate and mild level. Respondents with a high level of Depersonalization constitute 3.3% while 96.7% were at a moderate and mild level. Analysis show that 48.2% are at the high and moderate level for Personal Accomplishment while 51.7% is still at the lower level. Mean score for Personal Accomplishment